2022
DOI: 10.32604/cmes.2022.017756
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Mechanical Properties of Polycrystalline Mg Using Molecular Dynamics Simulation

Abstract: Magnesium (Mg) and its composites have been widely used in different fields, but the mechanical properties and deformation mechanisms of polycrystalline Mg (polyMg) at the atomic scale are poorly understood. In this paper, the effects of grain size, temperature, and strain rate on the tensile properties of polyMg are explored and discussed by the Molecular dynamics (MD) simulation method. The calculated results showed that there exists a critical grain size of 10 nm for the mechanical properties of polyMg. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Separate polycrystalline Mg and Al with different grain sizes, at a strain rate of 10 6 s −1 , were used to examine the potential influence of concurrent tension on the deformation behaviour and structural evolution of bonded Al and Mg, and the resulting stress-strain curves are presented in Figure 5a,b. It can be seen that, contrary to the study by Liu et al [30], no clear relationship between yield stress and grain size is observed for neither polycrystalline Mg nor Al at relatively low strain rates, while the elastic modulus rises with increasing grain size and the toughness increases with decreasing grain size. Similar to the stress fluctuations in the stress rise section of the Al/Mg layered composites mentioned earlier, the structural evolution of polycrystalline Mg is further analysed, as shown in Figure 6, where the stacking faults within the grains at a strain of 6.5% have been nucleated, the stress first reaches the peak, and then the stress decreases.…”
Section: Mechanical Response and Structural Evolution Of Al/mg Compos...contrasting
confidence: 93%
See 3 more Smart Citations
“…Separate polycrystalline Mg and Al with different grain sizes, at a strain rate of 10 6 s −1 , were used to examine the potential influence of concurrent tension on the deformation behaviour and structural evolution of bonded Al and Mg, and the resulting stress-strain curves are presented in Figure 5a,b. It can be seen that, contrary to the study by Liu et al [30], no clear relationship between yield stress and grain size is observed for neither polycrystalline Mg nor Al at relatively low strain rates, while the elastic modulus rises with increasing grain size and the toughness increases with decreasing grain size. Similar to the stress fluctuations in the stress rise section of the Al/Mg layered composites mentioned earlier, the structural evolution of polycrystalline Mg is further analysed, as shown in Figure 6, where the stacking faults within the grains at a strain of 6.5% have been nucleated, the stress first reaches the peak, and then the stress decreases.…”
Section: Mechanical Response and Structural Evolution Of Al/mg Compos...contrasting
confidence: 93%
“…The deformation behaviour of the polycrystalline system was simulated using the open-source Lammps software (LAMMPS 64-bit, version 3Nov2022-MPI; Simulation tool for particle-based materials modeling at the atomic, meso, and continuum scales; Sandia National Laboratories: Los Alamos, NM, USA, 2022) [ 44 ], and the results were analysed and visualised with Ovito [ 45 , 46 ], using the dislocation analysis (DXA) method and the common neighbour analysis (CNA) method. In Liu [ 30 ] and other recent studies, the Hall–Petch effect has been observed in Al and Mg polycrystalline models with a grainsize under 10 nm during tensile loading. The simulation boxes for polycrystalline Al and polycrystalline Mg were constructed with 10 nm length in each direction, containing 2, 4, 8, 16, and 32 grains at random, respectively.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations